2007
DOI: 10.1111/j.1365-294x.2007.03573.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for widespread cryptic sexual generations in apparently purely asexual Andricus gallwasps

Abstract: Oak gallwasps (Hymenoptera, Cynipidae, Cynipini) are one of seven major animal taxa that commonly reproduce by cyclical parthenogenesis (CP). A major question in research on CP taxa is the frequency with which lineages lose their sexual generations, and diversify as purely asexual radiations. Most oak gallwasp species are only known from an asexual generation, and secondary loss of sex has been conclusively demonstrated in several species, particularly members of the holarctic genus Andricus. This raises the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
33
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 71 publications
(206 reference statements)
3
33
1
Order By: Relevance
“…(b) Oak gallwasps as indicators of past floras Andricus hungaricus lies within a clade of Andricus species whose lifecycles require obligate alternation between two different taxonomic sections of the genus Quercus (Cook et al 2002;Stone et al 2008). The asexual generation always galls section Quercus sensu stricto oaks (such as Q. robur and Quercus petraea), while the sexual generation always galls section Cerris oaks (particularly Turkey oak, Quercus cerris).…”
Section: Discussion (A) Multispecies Interactionsmentioning
confidence: 99%
“…(b) Oak gallwasps as indicators of past floras Andricus hungaricus lies within a clade of Andricus species whose lifecycles require obligate alternation between two different taxonomic sections of the genus Quercus (Cook et al 2002;Stone et al 2008). The asexual generation always galls section Quercus sensu stricto oaks (such as Q. robur and Quercus petraea), while the sexual generation always galls section Cerris oaks (particularly Turkey oak, Quercus cerris).…”
Section: Discussion (A) Multispecies Interactionsmentioning
confidence: 99%
“…Likewise, a significant proportion of other Holarctic cynipine species are known from only one of the two generations (Melika 2006). Stone et al (2008) confirmed that many of these species actually do have a sexual generation (Stone et al 2008) and it is likely that alternate generation of many East Asian Dryocosmus species are yet to be described. The above mentioned uncertainties about the distribution, host association and biology of Eastern Palaearctic Dryocosmus species demonstrate that research on this taxon is still in its infancy.…”
Section: Discussionmentioning
confidence: 71%
“…The same host traits could thus potentially also structure parasitoid populations. Each of the approximately 150 oak gall wasp species in the Western Palaearctic has one spring generation and one autumn generation per year (Stone et al., 2008), providing the potential for parasitoids to evolve seasonal phenologies that allow attack of one or both generations. Gall wasp generations also show high host‐plant specificity, and in the Western Palaearctic, almost all oak cynipid galls develop only on oak species from one (but not both) of the native oak sections Quercus or Cerris (Stone et al., 2009).…”
Section: Introductionmentioning
confidence: 99%